CURRENT PHENOMENON TENSION OF THE UNITED STATES AND IRAN IN THE MIDDLE EAST - Rahman, Musyfiqur (Journal of Islamic World and Politics, 2020)
The tensions of the United States and Iran, as can be seen lately, have really reached a rare point in the many escalations in recent years in the Middle East. Apart from the historical factors that began since Iran succeeded in igniting the revolutionary fire by subverting the regime of Shah Mohamed Reza Pahlavi, another factor that further heightened the geopolitical dynamics of the region was the departure of the United States under President Donald Trump from nuclear agreement of the Joint Comprehensive Plan of Action (JCPOA) to tighten the geopolitical dynamics back economic sanctions for Iran. In this article, the writer tries to explain the phenomenon of tension between the two countries using the national interest theory according to Scott Burchill, by reading the strategic goals to be achieved from the political attitudes of the United States in the Middle East for its national interests.